ChemInform Abstract: Hydrogenation of Imines Catalyzed by 2‐(Aminomethyl)pyridine‐Based Ruthenium and Osmium Complexes. Issue 48 (10th November 2016) - Solinas, Maurizio; Sechi, Barbara; Baldino, Salvatore; Baratta, Walter; Chelucci, Giorgio
Abstract: Three Ru(II) and two Os(II) CNN pincer complexes are synthesized and tested in the title reaction.